2018
DOI: 10.1039/c7cp08358k
|View full text |Cite
|
Sign up to set email alerts
|

B2O3/SiO2 substitution effect on structure and properties of Na2O–CaO–SrO–P2O5–SiO2 bioactive glasses from molecular dynamics simulations

Abstract: The effect of B2O3/SiO2 substitution in SrO-containing 55S4.3 bioactive glasses on glass structure and properties, such as ionic diffusion and glass transition temperature, was investigated by combining experiments and molecular dynamics simulations with newly developed potentials. Both short-range (such as bond length and bond angle) and medium-range (such as polyhedral connection and ring size distribution) structures were determined as a function of glass composition. The simulation results were used to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 65 publications
8
43
0
Order By: Relevance
“…The simulated structures are found to be in good agreement with the experimental data. These applications together with our other recent work further validate that the new parameters are compatible with previous published parameters for other elements of the modified Teter parameterization.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The simulated structures are found to be in good agreement with the experimental data. These applications together with our other recent work further validate that the new parameters are compatible with previous published parameters for other elements of the modified Teter parameterization.…”
Section: Discussionsupporting
confidence: 84%
“…Addition of boron can also enhance bone repair and soft tissue healing. Due to the complex composition of bioactive glasses, molecular dynamics simulations have been used to extract the structural features of boron oxide‐containing bioactive glasses to correlate the structure, dynamics, and bioactivity behaviors of these novel bioactive glasses …”
Section: Resultsmentioning
confidence: 99%
“…With recent developments of potential parameters for B-O pairs together with earlier parameters for aluminosilicate glasses, 38,39 atomistic structural models of multicomponent borosilicate glasses can now be generated. 26,27,[40][41][42][43][44][45] These potential models include the composition-dependent partial charge pairwise potential, 38,39 a polarizable shell-model potential, 46 and an empirical interatomic potential. 47 In recent studies, the atomic-level structure model of ISG was successfully generated using partial charge potential with the composition-dependent potential parameters for B, 26,48 with excellent agreement to results of high energy X-ray diffraction, NMR, and extended X-ray adsorption fine structure (EXAFS) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limited availability of effective and transferable empirical potentials was the main hurdle in simulations of multicomponent borosilicate glasses. With recent developments of potential parameters for B‐O pairs together with earlier parameters for aluminosilicate glasses, 38,39 atomistic structural models of multicomponent borosilicate glasses can now be generated 26,27,40‐45 . These potential models include the composition‐dependent partial charge pairwise potential, 38,39 a polarizable shell‐model potential, 46 and an empirical interatomic potential 47 .…”
Section: Introductionmentioning
confidence: 99%
“…33 Furthermore, both MD simulations and experimental efforts reported relevant structural information around glass network that boron did not form a complete regular tetrahedral structure like silicon. 34,36 The results also showed that the structural units of the borate glass network included not only [BO 3 ] trihedrons but also [BO 4 ] tetrahedrons. It is well known that [BO 3 ] units are considered to reduce chemical durability and therefore make the dissolution rate faster.…”
Section: Introductionmentioning
confidence: 83%